High-expression of BCL10 inhibits cell-mediated immunity within the tumor immune microenvironment - Gu, Jinyi; Chen, Changshun; Chen, Yuanjing; Lv, Wei; Li, Fei; Zhu, Puyuan; He, Pu; Du, Yunjie; Liu, Huiling; Zhu, Bingdong (Frontiers in Immunology, 2025)
BackgroundB-cell lymphoma 10 (BCL10) is a key signaling molecule that plays a pivotal role in activating the NF-κB signaling pathway. However, it is unclear whether prolonged activation of BCL10 within tumors lead to T cell exhaustion and suppress immune responses against cancer.MethodsIn this study, through multi-layered bioinformatics analysis and experimental verification, the role of BCL10 on immune cells in the tumor immune microenvironment was systematically investigated. The correlation between BCL10 expression and infiltrated immune cells was analyzed by immune algorithms such as xCELL, CIBERSORT, QUANTISEQ and MCPcounter using TCGA and GTEx databases. Furthermore, single-cell RNA sequencing data of the cervical squamous cell carcinoma(CESC)microenvironment were analyzed using the GEO database. Moreover, an implanted CESC mice model was established, in which the expression and correlation of BCL10, NF-κB, and PD-1 in CD8+ T cells, as well as the proliferation and apoptosis of CD8+ T cells, were analyzed.ResultsIn silico analysis revealed that the upregulation of BCL10 in tumor immune microenvironment (TIME) was correlation with decreased infiltration of CD8+T cells, CD4+Th1 cells and NK T cells, and increased infiltration of Treg cells and CD4+Th2 cells in most tumors including CESC. In implanted CESC mice model, BCL10 expression was found upregulated in CD8+T cells, consequently activating the NF-κB signaling, and leading to upregulation of PD-1 expression, inhibiting proliferation of CD8+T cells, and promoting apoptosis of CD8+T cells.ConclusionsBCL10 is closely associated with immunosuppression across various tumor types. In CESC, chronic stimulation and over-activation by tumor antigens result in exhaustion of CD8+ T cells through the over-activation of the NF-κB signaling pathway and upregulation of PD-1 expression.